Understanding and managing HIV infection risk among men who have sex with men in rural Uganda: a qualitative study - Nakiganda, Lydia Jacenta; Bell, Stephen; Grulich, Andrew E.; Serwadda, David; Nakubulwa, Rosette; Poynten, Isobel Mary; Bavinton, Benjamin R. (BMC public health, 2021)
Background Same-sex sexual relations are criminalised in Uganda, and men who have sex with men (MSM) experience a high burden of HIV infection. In Uganda, health promotion policies focus on equity in healthcare and creating enabling environments. At present there is limited evidence upon which to enhance engagement of MSM in rural settings into effective HIV prevention. To fill this gap, our study explored MSM’s understandings of HIV risk and strategies used to reduce HIV risk in their sexual lives. Methods In-depth interviews were conducted with sixteen MSM in rural communities in Southwestern Uganda. Inductive thematic analysis examined men’s perceptions of HIV risk and strategies of reducing their own HIV risks. Results Understandings of HIV risk and risk practices were framed by lack of access to condoms, challenges negotiating condom and pre-exposure prophylaxis (PrEP) use, and condomless sex being reported as more pleasurable than sex with condoms. Strategies men perceived as enabling them to manage HIV risk included: PrEP use; condom use; knowing partners’ HIV status; avoiding partners associated with HIV risk; oral sex; withdrawal before ejaculation and washing one’s penis after sex. There were several misconceptions arising from poor HIV prevention knowledge. Strategies reliant on communication and negotiation with sexual partners were inhibited by gendered powered imbalances. Conclusions Our findings illustrate that MSM in rural settings in Uganda are making concerted efforts to implement strategies that might reduce risk of HIV transmission and infection within their sexual relationships. Key HIV health promotion and service-related strategies to support MSM with these efforts include an effective condom and lubricant supply chain; a PrEP program in trusted local health units, implemented via discreet community-outreach mechanisms; and same-sex specific HIV-related health promotion.